Exploring AI governance in the Middle East and North Africa (MENA) region: gaps, efforts, and initiatives - Hana Trigui; Fatma Guerfali; Emna Harigua-Souiai; Radwan Qasrawi; Chiraz Atri; Elie Salem Sokhn; Christo El Morr; Karima Hammami; Oussama Souiai; Jianhong Wu; Jude Dzevela Kong; Jean Jacques Rousseau; et al. (Data & Policy)
This commentary explores MENA”s AI governance, addressing gaps, showcasing successful strategies, and comparing national approaches. It emphasizes current deficiencies, highlights regional contributions to global AI governance, and offers insights into effective frameworks. The study reveals distinctions and trends in MENA”s national AI strategies, serving as a concise resource for policymakers and industry stakeholders.